Anselm of Canterbury and the Many Senses of “Being”. A Comparison Between the Argument of the Proslogion and the Regula of the Monologion: A comparison between the argument of the Proslogion and the regula of the Monologion - Guerrero-Troncoso, Hernán (Ruch Filozoficzny, 2022)
This article makes a comparison between Anselm’s so-called “ontological argument” of the Proslogion and the regula he established in the Monologion. This regula would allow, under a certain respect, to consider existence as a perfection attributable to God, even though it does not possess the same ontological status of any other attribute, i.e., it should not be considered what Kant calls a “real predicate”. Consequently, it is possible to outline the different senses in which Anselm understands the notion of “being” and the conditions under which existence and real perfection can transcend the sphere of creatures and in help conceiving God. This distinction of the senses of being would later allow for existence to be considered a perfection, just as real predicates are, but according to a completely different meaning.